ENDOILLUMINATION-ASSISTED MODIFIED SCLERAL BUCKLING. Issue 2 (February 2018) - Assi, Alexandre; Abdelmassih, Youssef; El-Khoury, Sylvain
Abstract : Purpose: To assess the anatomical and functional outcomes in addition to complications for endoillumination-assisted modified scleral buckling surgery using a noncontact Oculus BIOM wide-angle viewing system in patients with primary rhegmatogenous retinal detachment. Methods: This is an interventional prospective noncomparative case series. Consecutive patients listed for scleral buckle surgery for primary rhegmatogenous retinal detachment were enrolled over an 18-month period and followed up for 1 year. The study cohort consisted of 25 patients (25 eyes) of which 23 patients (23 eyes) completed the 1-year follow-up. Scleral buckling surgery was done with a 23-gauge endoillumination probe, which was inserted through a pars plana sclerotomy. The primary outcome measure was anatomical success rate with one surgery assessed at the 6-month and the 1-year follow-up. Secondary outcome measures included final visual acuity, number of surgeries required, and complication rates such as entry site break, posterior vitreous detachment, endophthalmitis, and cataract. Results: At 1 year, anatomical success with one surgery was achieved in 20 patients (87%). One patient required two additional vitreoretinal surgeries and 2 patients required three additional surgeries. All patients had a flat retina at 1 year with silicone oil present in one eye. Mean best-corrected visual acuity improved by six ETDRS lines, from 1.03 ± 0.83 logarithm of the minimum angle of resolution (20/200) preoperatively to 0.40 ± 0.47 logarithm of the minimum angle of resolution (20/50) at 1 year. No entry site breaks were detected, and posterior vitreous detachment developed in six patients (26%). No cases of endophthalmitis or cataract progression were reported. Conclusion: Endoillumination-assisted modified scleral buckling surgery combined with a noncontact wide-angle viewing system can provide good anatomical and functional outcomes with many advantages and a low complication rate. Abstract : This study reports about the success rate, the visual outcome, and the complication rate of scleral buckle surgery, in which indirect ophthalmoscopy is replaced by an endoillumination probe. Success rates are comparable with conventional scleral buckling.